Cytopenia after chimeric antigen receptor T cell immunotherapy in relapsed or refractory lymphoma - Zhou, Jin; Zhang, Ying; Shan, Meng; Zong, Xiangping; Geng, Hongzhi; Li, Jiaqi; Chen, Guanghua; Yu, Lei; Xu, Yang; Li, Caixia; Wu, Depei (Frontiers in Immunology, 2022)
Background: Patients with relapsed or refractory (R/R) lymphomas have benefited from chimeric antigen receptor (CAR)-T-cell therapy. However, this treatment is linked to a high frequency of adverse events (AEs), such as cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and haematologic toxicity. There has been increasing interest in haematological toxicity in recent years, as it can result in additional complications, such as infection or haemorrhage, which remain intractable. Methods: We conducted a retrospective, single-institution study to evaluate the patterns and outcomes of cytopenia following CAR-T-cell infusion and potential associated factors. Results: Overall, 133 patients with R/R lymphoma who received CAR-T-cell therapy from June 2017 to April 2022 were included in this analysis. Severe neutropenia, anemia and thrombocytopenia occurred frequently (71, 30 and 41%, respectively) after CAR-T-cell infusion. A total of 98% of severe neutropenia and all severe thrombocytopenia cases occurred in the early phase. Early severe cytopenia was associated with CRS incidence and severity, as well as peak inflammatory factor (IL-6, C-reactive protein (CRP), and ferritin) levels. In multivariate analysis, prior haematopoietic stem cell transplantation (HSCT), baseline haemoglobin (HB), and lymphodepleting chemotherapy were independent adverse factors associated with early severe cytopenia. In addition, 18% and 35% of patients had late neutrophil- and platelet (PLT)-related toxicity, respectively. In multivariate analysis, lower baseline PLT count was an independent factor associated with late thrombocytopenia. More severe cytopenia was associated with higher infection rates and poorer survival. Conclusions: This research indicates that improved selection of patients and management of CRS may help to decrease the severity of cytopenias and associated AEs and improve survival following CAR-T-cell therapy.